Rozwiąże ktoś mi te działania plis
4y-6x+4x^2-5(x-y)
3xy-(-2)-3(2xy-2)
(4a-8b)-(3a-3b)*(-5)
-a(4a-a)-a(2a-5a)
-(2+a)-(2a+1)*(-5)


Odpowiedź :

Szczegółowe wyjaśnienie:

W razie niejasności, pisz.

Zobacz obrazek Monikaczekol

[tex]4y - 6x + 4x^{2}-5(x-y) = 4y-6x+4x^{2}-5x+5y = 4x^{2}-11x+9y[/tex]

[tex]3xy - (-2) -3(2xy-2) = 3xy + 2 - 6xy + 6 = -3xy+8[/tex]

[tex](4a-8b)-(3a-3b)\cdot(-5) =4a-8b+15a - 15b = 19a - 23b[/tex]

[tex]-a(4a-a) - a(2a-5a) = -a\cdot3a - a\cdot(-3a) = -3a^{2}+3a^{2} = 0[/tex]

[tex]-(2+a)-(2a+1)\cdot(-5) = -2-a+10a+5 = 9a+3[/tex]